Translocation of threatened plants as a conservation measure in China. Issue 6 (15th September 2015) - Liu, Hong; Ren, Hai; Liu, Qiang; Wen, XiangYing; Maunder, Michael; Gao, JiangYun
Abstract: We assessed the current status of plant conservation translocation efforts in China, a topic poorly reported in recent scientific literature. We identified 222 conservation translocation cases involving 154 species, of these 87 were Chinese endemic species and 101 (78%) were listed as threatened on the Chinese Species Red List. We categorized the life form of each species and, when possible, determined for each case the translocation type, propagule source, propagule type, and survival and reproductive parameters. A surprisingly large proportion (26%) of the conservation translocations in China were conservation introductions, largely implemented in response to large‐scale habitat destruction caused by the Three‐Gorge Dam and another hydropower project. Documentation and management of the translocations varied greatly. Less than half the cases had plant survival records. Statistical analyses showed that survival percentages were significantly correlated with plant life form and the type of planting materials. Thirty percent of the cases had records on whether or not individuals flowered or fruited. Results of information theoretic model selection indicated that plant life form, translocation type, propagule type, propagule source, and time since planting significantly influenced the likelihood of flowering and fruiting on the project level. We suggest that the scientific‐based application of species conservation translocations should be promoted as part of a commitment to species recovery management. In addition, we recommend that the common practice of within and out of range introductions in nature reserves to be regulated more carefully due to its potential ecological risks. We recommend the establishment of a national office and database to coordinate conservation translocations in China. Our review effort is timely considering the need for a comprehensive national guideline for the newly announced nation‐wide conservation program on species with extremely small populations, which is expected to stimulate conservation translocations for many species in the near future.